UPV-CMT (ROTC) Unit its chaging program of instruction (1947-1987). - Soriano, Enriquito M. III. (1987.)
Based on the findings of the study, the UPV-CMT Unit was established as a result of Commonwealth Act No. 1 commonly known as the National Defense Act of 1935, which provided that "at such colleges and universities as the President may designate, there shall be established and maintained Reserve Officer Training Corps Units of such arm or service as he shall specify, where every physically fit student shall be required to pursue a course of military instruction . . . " The main concept behind this act was the preparation of the individual especially the youth for the defense of the country in the event of an external threat. Moreover, the unit was also established to produce officers for the reserve component of the Armed Forces of the Philippines and to qualify students for positions of leadership in the military as well as civilian organizations., There were notable changes in the POIs during the following periods (Huk Insurgency period up to the Aquino Administration) as gleaned from documents, memorandums and office files. Although these changing POIs were fluid from one period to another, nonetheless there was a remarkable transformation and/or improvement as the case may be in some cases during the different periods. The rise of the Huk Insurgency and CPP/NPA Insurgency prompted the military establishment to reexamine and change its American patterned national defense posture, with the main contention that it was not suited to counter the guerilla type warfare the Huks conducted. So as reassessment of the POIs in the higher and lower echelons of the AFP in which the UPV-CMT was a part, brought with it the introduction of a new type of warfare known as unconventional warfare (UW). It's emphasis concentrated in countering the rebels with the same type of warfare the latter were using. Throughout the Marcos era this type of warfare was used and even modified, the concept during that period as based on the instructions of the Unit was the emergence of the soldier as both a fighter and simultaneously a builder. It enabled the soldier to contribute its share in the task of nation-building. The youth, on the other hand were made aware and responsive to their military and civil obligations to the country. The rise of the Aquino Administration provided the unit with another POI, that is the thrust of reconciling the people and changing the image of military establishment. Although this orientation served only as an addition to the concept modified in the previous administration and even though events are still unfolding nonetheless we can see a clear manifestation of the military as the true protector and partner of the people. In conclusion, therefore, we, can say that changes in the national security concepts of our country as reflected in the changing thrust of the ROTC program is dependent on the national security conditions of the country and is in turn due to various factors (e.g. social, political, and economic).
Thesis (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the philippines in the Visayas, Miagao, Iloilo.
Keywords: CMT, UPV (ROTC) -- 1947-1987.